Penyalahgunaan Pembayaran Pajak Kendaraan Bermotor Pemerintah Berdasarkan Peraturan Daerah Nomor 6 Tahun 2010 - Stefanus Kehi; Salmon Eliazer Marthen Nirahua; Heillen Martha Yosephine Tita (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Motor vehicle tax is one type of tax that is increasing, in line with the needs of the state. In Law number 28 of 2009, concerning regional taxes and levies, it is explained that motor vehicle tax is a tax on ownership and control of motorized vehicles. The Maluku Provincial Government in responding to the authority given to manage finances issued Regional Regulation Number 6 of 2010 concerning Motor Vehicle Taxes.Purposes of the Research: This study aims to analyze, as well as review and discuss the misuse of government Motor Vehicle Tax based on regional Regulation No. 6 of 2010. Methods of the Research: The research method that is used with the type of normative research, in this writing is used to approach the problem of legislation and conceptual approach. Furthermore, the legal materials used are primary, secondary and tertiary legal materials. Procedures and collection of legal materials through the study of literature and processing of legal materials analysis, analysis is carried out using a description method using qualitative methods.Results of the Research: The results showed that the government Motor Vehicle Tax that occurs in the scope of Maluku province is the occurrence of abuse. This can be seen clearly in the case under review where one DPRD Office official did not replace the lat of the government vehicle number he bought from the local government. With the mode that by still using black motor vehicle license plates in order to pay less tax than other motor vehicles that have black license plates. Furthermore, it cannot be directly said that the taxpayer's fault, but also from the office in this case the Maluku Provincial Revenue Service which regulates government Motor Vehicle Tax.